The superior properties of spark plasma sintered La-Fe-Si magnetocaloric alloys - Wu, Yu-Cai (2023)
LaFe11.8Si1.2 bulk magnetocaloric materials were prepared by hot-pressing sintering (HPS) and spark plasma sintering (SPS) techniques. The effects of the particle size, phase content and porosity on the thermal conductivity, mechanical and magnetocaloric properties were studied. Our results demonstrated that the reduction of porosity in bulk magnetocaloric materials was an effective way to enhance the magnetocaloric effect. Compared to the HPS samples, the porosity of the SPS samples, with an initial powder size of 100−200 μm, reduced by 18%, which resulted in (−ΔSM)max and (−ΔSM)Vmax increasing by 15% and 19%, respectively. The SPS samples had a large (−ΔSM)max value in the range of 7.3‒12.8 J/kg·K (μ0ΔH=2T), good maximum compressive strength of 216‒636 MPa and thermal conductivity of 5.8‒7.6 W/m·K. Thus, SPS has been shown to be a promising processing technology to fabricate magnetocaloric materials (MCMs) with excellent performance.